2017
DOI: 10.1097/prs.0000000000003156
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Reconstruction of Traumatic Lower Extremity Defects in the Pediatric Population

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 32 publications
5
72
2
1
Order By: Relevance
“…It has been found that pediatric vessels may be less liable to spasm due to less development of the muscle layer of the vessels. 12 Besides, Momeni et al 13 noticed in his series another interesting fact, namely a lack of atherosclerosis and intimal damage secondary to long-term vascular disease as well as the absence of venous insufficiencies common in adults. 13 Overall, compared with adults, children have better functional and sensory recovery capacity making these operations worthwhile even though they may be technically more difficult.…”
Section: Discussionmentioning
confidence: 97%
“…It has been found that pediatric vessels may be less liable to spasm due to less development of the muscle layer of the vessels. 12 Besides, Momeni et al 13 noticed in his series another interesting fact, namely a lack of atherosclerosis and intimal damage secondary to long-term vascular disease as well as the absence of venous insufficiencies common in adults. 13 Overall, compared with adults, children have better functional and sensory recovery capacity making these operations worthwhile even though they may be technically more difficult.…”
Section: Discussionmentioning
confidence: 97%
“…Revisionsoperationen werden in etwa 10 % der Fälle notwendig. Mit einem Lappenverlust ist in etwa 5 % zu rechnen [27,28].…”
Section: Soft Tissue Reconstruction Of Hands and Feet In Childhood Abunclassified
“…Other studies report lower success rates, including the 4.8% flap failure rate reported by Starnes-Roubaud et al in this month's issue of Annals of Surgical Oncology, and a 2.2% failure rate reported by Jacob et al 2 In the trauma or mixed trauma/ oncology literature, flap success rates ranging from 85.3 to 96.4% have been observed, with most being at the higher end of that range. [4][5][6] Such acceptable rates of flap success indicate pediatric microsurgery is technically possible, and Upton and Guo, and others, have rejected the notion that pediatric vessels are innately more prone to spasm. 3 Instead, anastomotic challenges are more likely due to error in technique or vessel handling, and even with small, spastic vessels, success is possible, as supported by the pediatric replantation literature.…”
Section: Editorialmentioning
confidence: 99%